Co-doped hollow spherical piezoelectric catalyst as well as preparation method and application thereof
The activation of PMS by Co-doped hollow spherical BiFeO3 piezoelectric catalyst solves the problem of insufficient catalytic activity of PMS in the prior art, and achieves efficient degradation of organic pollutants in antibiotic wastewater, with good application prospects.
Patent Information
- Application Number
- CN202411485216.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-07
AI Technical Summary
The existing advanced oxidation process based on permonomerol (PMS) has insufficient charge separation performance and active center regeneration kinetics, limiting its application in environmental governance.
Co-doped hollow spherical BiFeO3 piezoelectric catalyst is used to activate PMS through piezoelectric effect to improve its catalytic activity. The catalyst is synthesized by a solvent induction strategy and has high specific surface area, multiple reactive sites, good piezoelectric properties and structural stability.
It significantly improves the catalytic activity and energy efficiency of PMS, and achieves efficient degradation of organic pollutants in antibiotic wastewater. It has simple process, convenient operation, low cost, and has great application prospects.
Smart Images

Figure CN119386884A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material preparation and environmental catalysis, and specifically relates to a Co-doped hollow spherical BiFeO3 piezoelectric catalyst and a preparation method and application thereof. Background Art
[0002] Advanced oxidation processes (AOPs) have attracted increasing attention from researchers as an effective method for mineralization of pollutants. At present, advanced oxidation methods include Fenton oxidation, Fenton-like oxidation, photocatalytic oxidation, electrochemical oxidation, chlorine oxidation, ozone oxidation, ultrasonic irradiation, etc. Most of these traditional oxidation processes have disadvantages such as high energy consumption, harsh reaction conditions, and incomplete treatment of pollutants. Among them, the advanced oxidation process based on permonosulfate (PMS) is popular because of its ability to efficiently degrade refractory organic matter in wastewater over a wide pH range. Generally, the activation of PMS can be achieved by inputting energy or chemicals (such as heat, light, ultrasound, alkali, and low-valent transition metals). Peroxide-based advanced oxidants have great potential in degrading antibiotics in wastewater due to their advantages such as high oxidation ability and low cost. Peroxide bonds can generate highly active reactive oxygen species (ROS) through energy and electron transfer reactions, hydrogen abstraction reactions, or electrophilic addition reactions. In the advanced oxidation technology of activated PMS, free radical pathways and non-radical pathways play a vital role in the degradation of pollutants. However, the charge separation performance of PMS-based advanced oxidation technology is poor and the active site regeneration kinetics is slow, which limits its application in environmental governance. Therefore, accelerating the regeneration of active sites is crucial to improving the catalytic activity of PMS.
[0003] In recent years, researchers have proposed a strategy to accelerate the regeneration of active centers by activating PMS through piezoelectric catalysis. Piezoelectric catalysis is a technique that uses piezoelectric materials to promote the separation of electron-hole pairs through the piezoelectric effect, thereby producing active substances such as ·OH, H2O2, and ·O2 − Green and environmentally friendly technology for degrading water pollutants. Piezoelectric catalysis is not limited by sunlight and can utilize and recycle waste mechanical energy. It has great application potential in the environmental and energy fields. Applying the piezoelectric effect to semiconductor materials to generate a built-in electric field through piezoelectric polarization can effectively regulate the formation and transmission of electrons and holes. In addition, the electrons and holes generated in piezoelectric catalysis are expected to react with PMS to produce reactive oxygen species (ROS). BiFeO3 (BFO) is a representative piezoelectric material with a piezoelectric coefficient (d33) of 100pmV -1 , spontaneous polarization exceeds 100 μC cm −2These properties make it an ideal candidate for piezoelectric catalysis. In addition, BFO has the typical ABO3 structure of perovskite, which gives it special chemical design versatility, engineering defect capabilities, tunable surface properties and stability. Combining BFO with PMS and piezoelectric effect can improve the reaction activity and energy efficiency of the system, which is of great significance for the efficient use of persulfate to degrade antibiotics in water. Summary of the invention
[0004] The present invention provides a Co-doped hollow spherical BiFeO3 piezoelectric catalyst which has a high specific surface area, multiple reaction active sites, good piezoelectric performance, stable structure and can efficiently activate persulfate. The present invention also provides a method for preparing the Co-doped hollow spherical BiFeO3 piezoelectric catalyst which has the advantages of simple process, convenient operation, low cost, high preparation efficiency and high yield. The present invention also provides the application of the Co-doped hollow spherical BiFeO3 piezoelectric catalyst in treating antibiotic wastewater.
[0005] The present invention adopts the following technical solutions to achieve the above purpose: 1. Dissolve iron salt, bismuth salt and cobalt salt in a mixed solvent of isopropanol and glycerol; The molar ratio of the iron salt, the bismuth salt and the cobalt salt is 1:1:0.1-0.5, and the mixed solvent of isopropanol and glycerol is prepared by mixing isopropanol and glycerol in a volume ratio of 3-6:1; 2. Place the mixture in step 1 at 180-250° C. for hydrothermal reaction for 12 hours, separate the solid and the liquid, wash the solid with deionized water and anhydrous ethanol, dry, and calcine in an air atmosphere at 400-600° C. to obtain a Co-doped hollow spherical piezoelectric catalyst; 3. Use Co-doped hollow spherical BiFeO3 piezoelectric catalyst to activate persulfate to degrade antibiotics in water. Specifically, the Co-doped hollow spherical BiFeO3 catalyst is mixed with antibiotic wastewater, and persulfate is added. Under constant temperature and ultrasonic conditions, efficient degradation of antibiotics can be achieved.
[0006] Compared with the prior art, the present invention has the following advantages: (1) The present invention successfully synthesized a catalyst with a hollow spherical morphology by using a solvent-induced strategy. Compared with typical bulk materials, the hollow structure has higher flexibility and larger deformation under ultrasound, and the diffusion path of ion transport is short and the piezoelectric potential is high, which is beneficial to improving the performance of piezoelectric catalysts. Applying the piezoelectric effect to semiconductor materials can effectively regulate the formation and transmission of electrons and holes by generating a built-in electric field through piezoelectric polarization. In addition, the electrons and holes generated in piezoelectric catalysis are expected to react with PMS to produce active oxygen. (2) The present invention adopts a simple hydrothermal synthesis to successfully dope Co into the hollow spherical BiFeO3 catalyst. The Co-doped BFO can not only promote polarization, but also the induced oxygen vacancies can provide electron capture sites and promote the separation of electron-hole pairs from the band structure under ultrasonic treatment; hBFCO provides stronger adsorption capacity for O2 and H2O molecules and increases the efficiency of active oxygen generation; at the same time, the preparation method of the present invention is also simple in process, convenient in operation, easy to obtain raw materials, low in cost, easy to realize industrial production, and has great application prospects, especially in the field of environmental catalysis; (3) The catalyst prepared by the present invention is mixed with antibiotic wastewater to achieve effective degradation of organic pollutants under constant temperature oscillation or ultrasonic conditions, which has the advantages of simple process, convenient operation, low cost, high treatment efficiency and good degradation effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 This is the SEM image of the catalyst hBFCO of Example 1; Figure 2 The XRD patterns of the catalysts prepared in Example 1 and Comparative Example 1; Figure 3 The XRD diagrams of the catalysts prepared in Comparative Examples 2 and 3; Figure 4 This is the SEM image of the catalyst BFCO of Comparative Example 3; Figure 5 It is a time-degradation efficiency diagram of the degradation of CTC by piezoelectrically activated PMS of the catalysts of Example 1 and Comparative Examples 1-3; Figure 6 It is a fitting diagram of the degradation rate constant of the degradation of CTC by the piezoelectric activation of PMS by the catalysts of Example 1 and Comparative Examples 1-3; Figure 7 This is a time-degradation efficiency diagram of the catalyst in Example 1 for degrading CTC under oscillation, ultrasound, and PMS conditions; Figure 8 This is a fitting diagram of the decomposition rate constant of the catalyst in Example 1 for degradation of CTC under oscillation, ultrasound and PMS conditions. DETAILED DESCRIPTION
[0008] It should be understood that the embodiments of the present invention shown in the exemplary embodiments are only illustrative. Although only a few embodiments are described in detail in the present invention, it is easy for those skilled in the art to appreciate that multiple modifications are feasible without actually departing from the teaching of the subject matter of the present invention. Accordingly, all such modifications should be included within the scope of the present invention. Without departing from the gist of the present invention, other replacements, modifications, changes and deletions may be made to the design, operating conditions and parameters of the following exemplary embodiments.
[0009] Example 1: Preparation of Co-doped hollow spherical bismuth ferrite catalyst 1. Take 0.2909g of ferric nitrate nonahydrate, 0.3493g of bismuth nitrate pentahydrate and 0.0717g of cobalt acetate tetrahydrate and dissolve them in a mixed solvent of isopropanol and glycerol (prepared by mixing 30mL of isopropanol and 6mL of glycerol), and dissolve them by stirring or ultrasound-assisted dissolution until the solution is clear; transfer the mixed solution to a 50mL autoclave, and hydrothermally react at 200℃ for 12 hours. After natural cooling, filter, rinse the solid with deionized water and anhydrous ethanol twice each, and dry it at 60℃ for 3 hours to obtain a precursor; place the precursor in a corundum crucible, put it in a muffle furnace, heat it to 550℃ at a heating rate of 3℃ / min and keep it warm for 2 hours, and take it out after natural cooling to obtain a dark gray powder Co-doped hollow spherical BiFeO3 catalyst, named hBFCO, and the SEM image of the catalyst hBFCO is shown in Figure 1 From the figure, we can see that it is a hollow spherical structure; its XRD diagram is shown in Figure 2 From the figure, it can be seen that the intensity and position of some peaks have changed significantly after doping, and Bi 7.53 Co 0.47 O 11.92 (PDF#49-1762) Card peaks, indicating that Co was successfully doped into hBFO.
[0010] Comparative Example 1: Preparation of Hollow Spherical Bismuth Ferrite 0.2909 g of ferric nitrate nonahydrate and 0.3493 g of bismuth nitrate pentahydrate were dissolved in a mixed solvent of isopropanol and glycerol (prepared by mixing 30 mL of isopropanol and 6 mL of glycerol), and the solution was dissolved by stirring or ultrasound-assisted dissolution until the solution was clear; the mixed solution was transferred to a 50 mL autoclave, reacted at 200 ° C for 12 h, and filtered after natural cooling. The solid was rinsed with deionized water and anhydrous ethanol twice each, and dried at 60 ° C for 3 h to obtain a precursor; the precursor was placed in a corundum crucible, placed in a muffle furnace, heated to 550 ° C at a heating rate of 3 ° C / min and kept warm for 2 h, and taken out after natural cooling to obtain an orange powder hollow spherical BiFeO3 catalyst, named hBFO, and its XRD pattern is shown in Figure 2 ,It can be seen from the figure that its peak corresponds one to one with the peak of BiFeO3 (PDF#20-0169), proving that hBFO was successfully prepared.
[0011] Comparative Example 2: Preparation of bismuth ferrite 0.2909 g of ferric nitrate nine hydrate and 0.3493 g of bismuth nitrate pentahydrate were dissolved in 36 mL of deionized water, and the mixture was dissolved by stirring or ultrasound. The mixture was transferred to a 50 mL autoclave, reacted at 200 ° C for 12 h, and filtered after natural cooling. The solid was rinsed with deionized water and anhydrous ethanol twice each, and dried at 60 ° C for 3 h to obtain a precursor. The precursor was placed in a corundum crucible, placed in a muffle furnace, heated to 550 ° C at a heating rate of 3 ° C / min and kept warm for 2 h, and taken out after natural cooling to obtain a reddish brown powder BiFeO3 catalyst, named BFO, and its XRD pattern is shown in Figure 3 ,It can be seen from the figure that its peak corresponds one to one with the peak of BiFeO3 (PDF#20-0169), proving that BFO was successfully prepared.
[0012] Comparative Example 3: Preparation of Co-doped bismuth ferrite 0.2909 g of ferric nitrate nonahydrate, 0.3493 g of bismuth nitrate pentahydrate and 0.0717 g of cobalt acetate tetrahydrate were dissolved in 36 mL of deionized water, and the solution was dissolved by stirring or ultrasound. The mixed solution was transferred to a 50 mL autoclave, reacted at 200 ° C for 12 h, and filtered after natural cooling. The solid was rinsed with deionized water and anhydrous ethanol twice each, and dried at 60 ° C for 3 h to obtain a precursor. The precursor was placed in a corundum crucible, placed in a muffle furnace, heated to 550 ° C at a heating rate of 3 ° C / min and kept warm for 2 h, and taken out after natural cooling to obtain a black powder Co-doped BiFeO3 catalyst, named BFCO. The SEM image of the catalyst BFCO is shown in Figure 4 , BFCO catalyst is in block form; its XRD pattern is shown in Figure 3 From the figure, it can be seen that the intensity and position of some peaks have changed significantly after doping, and Bi 7.53 Co 0.47 O 11.92 (PDF#49-1762) Card peaks, indicating that Co was successfully doped into BFO.
[0013] Example 2: Application of the catalysts in Example 1 and Comparative Examples 1-3 in treating antibiotic wastewater The catalyst hBFCO of Example 1, the catalyst hBFO of Comparative Example 1, the catalyst BFO of Comparative Example 2, and the catalyst BFCO of Comparative Example 3 were weighed, 30 mg each, and placed in 40 mL of a 10 mg / L chlortetracycline hydrochloride (CTC) solution, and then 36.9 mg of potassium persulfate (PMS) was added to the chlortetracycline hydrochloride solution, and the solution was placed under ultrasound for catalytic degradation reaction. 3 mL of the reaction solution was taken at 5 min, 10 min, 15 min, and 20 min, respectively, and the absorbance value of chlortetracycline hydrochloride in the solution was measured with a spectrophotometer, and the degradation efficiency of chlortetracycline hydrochloride by different catalysts under different time conditions was calculated.
[0014] Results Figure 5 As can be seen from the figure, the hBFCO catalyst exhibits the best catalytic performance, degrading 99.34% of chloramphenicol hydrochloride in 15 minutes and 100% of chloramphenicol hydrochloride in 20 minutes, indicating that the hBFCO catalyst can efficiently activate PMS to produce a large amount of ROS under piezoelectric conditions.
[0015] The degradation rate fitting results are shown in Figure 6 From the figure, it can be seen that the degradation rate of chlortetracycline hydrochloride by catalyst hBFCO is several times that of other catalysts, indicating that the catalytic performance of catalyst hBFCO is excellent.
[0016] Example 3: Experiment of treating antibiotic wastewater with the catalyst hBFCO in Example 1 under different conditions 1. Weigh 20 mg of the catalyst of Example 1 and place each in 40 mL of 10 mg / L chlortetracycline hydrochloride solution, and perform catalytic degradation reaction under oscillation (hBFCO) and ultrasound (hBFCO+US) conditions respectively; 2. Weigh 20 mg of the catalyst of Example 1 and 24.6 mg of PMS, respectively, and place them in 40 mL of 10 mg / L chlortetracycline hydrochloride solution, and perform catalytic degradation reaction under oscillation (hBFCO+PMS) or ultrasound (hBFCO+PMS+US) conditions; 3. Weigh 24.6 mg of PMS and place it in 40 mL of 10 mg / L chlortetracycline hydrochloride solution, and perform catalytic degradation reaction under ultrasonic conditions (PMS+US); 3 mL of the reaction solution was taken at 5 min, 10 min, 15 min and 20 min respectively, and the absorbance of chlortetracycline hydrochloride in the solution was measured by a spectrophotometer, and the degradation efficiency of chlortetracycline hydrochloride by different catalysts under different time conditions was calculated.
[0017] Results Figure 7From the figure, it can be seen that hBFCO has the best degradation rate when PMS is added and under ultrasonic conditions. The degradation effect reaches 94.45% at 15 minutes and 98.36% at 20 minutes, indicating that PMS can be activated more quickly under piezoelectric conditions to produce more active substances.
[0018] The degradation rate fitting results are shown in Figure 8 From the figure, it can be seen that the degradation rate of chlortetracycline hydrochloride by piezoelectric activation of PMS by catalyst hBFCO is several times that of pure adsorption, pure Fenton and pure piezoelectric degradation of chlortetracycline hydrochloride, indicating that hBFCO can better activate PMS under piezoelectric conditions.
[0019] Example 4: Preparation of Co-doped hollow spherical piezoelectric catalyst 1. Take 0.2909g of ferric nitrate nine hydrate, 0.3493g of bismuth nitrate pentahydrate and 0.0179g of cobalt acetate tetrahydrate and dissolve them in a mixed solvent of isopropanol and glycerol (prepared by mixing 24mL of isopropanol and 6mL of glycerol), and dissolve them by ultrasound until the solution is clear; transfer the mixed solution to a 50mL autoclave, hydrothermally react at 200℃ for 12h, and filter after natural cooling. The solid is rinsed with deionized water and anhydrous ethanol twice each, and then dried at 60℃ for 3h to obtain a precursor; place the precursor in a corundum crucible, put it in a muffle furnace, heat it to 500℃ at a heating rate of 3℃ / min and keep it warm for 2h, and take it out after natural cooling to obtain a Co-doped hollow spherical BiFeO3 catalyst; 2. Add 20 mg of the catalyst prepared in step 1 and 24.6 mg of PMS to 40 mL of 10 mg / L chlortetracycline hydrochloride solution. After 20 min of treatment, the degradation rate of chlortetracycline hydrochloride was 84.28%.
[0020] Example 5: Preparation of Co-doped hollow spherical piezoelectric catalyst 1. Take 0.2909g of ferric nitrate nine hydrate, 0.3493g of bismuth nitrate pentahydrate and 0.0717g of cobalt acetate tetrahydrate and dissolve them in a mixed solvent of isopropanol and glycerol (prepared by mixing 30mL of isopropanol and 6mL of glycerol), and dissolve them by ultrasound assistance until the solution is clear; transfer the mixed solution to a 50mL autoclave, and hydrothermally react at 180°C for 12 hours. After natural cooling, filter, rinse the solid with deionized water and anhydrous ethanol twice each, and dry it at 60°C for 3 hours to obtain a precursor; place the precursor in a corundum crucible, put it in a muffle furnace, heat it to 500°C at a heating rate of 3°C / min and keep it warm for 2 hours, and take it out after natural cooling to obtain a Co-doped hollow spherical BiFeO3 catalyst; 2. Add 20 mg of the catalyst prepared in step 1 and 24.6 mg of PMS to 40 mL of 10 mg / L chlortetracycline hydrochloride solution. After 20 min of treatment, the degradation rate of chlortetracycline hydrochloride was 93.31%.
Claims
1. A method for preparing a Co-doped hollow spherical piezoelectric catalyst, characterized in that: Iron salt, bismuth salt and cobalt salt are added to a mixed solvent of isopropanol and propylene glycol, and a hydrothermal reaction is carried out at 180-250°C for 12 hours. The solid and liquid are separated, and the solid is washed with deionized water and anhydrous ethanol. After drying, the solid is calcined in an air atmosphere at 400-600°C to obtain a Co-doped hollow spherical piezoelectric catalyst.
2. The method for preparing the Co-doped hollow spherical piezoelectric catalyst according to claim 1, characterized in that: The molar ratio of iron salt: bismuth salt: cobalt salt is 1:1:0.1-0.5, and the mixed solvent of isopropanol and glycerol is prepared by mixing isopropanol and glycerol in a volume ratio of 3-6:
1.
3. A Co-doped hollow spherical piezoelectric catalyst prepared by the method for preparing a Co-doped hollow spherical piezoelectric catalyst according to any one of claims 1 to 2.
4. Use of the Co-doped hollow spherical piezoelectric catalyst according to claim 3 in treating antibiotic wastewater.